Granulocyte-macrophage colony-stimulating factor: expression and regulation in human immune responses with relevance to multiple sclerosis - Aram, Jehan Jalal (2018)
Background: Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF) is a haematopoietic growth factor and a pro-inflammatory cytokine produced by T cells and other immune cells. Recent evidence suggests that GM-CSF plays an important role in multiple sclerosis (MS) pathogenesis. Few recent studies have detected GM-CSF expression by immune cells in MS. In this thesis, the expression of GM-CSF and its receptor by different subtypes of peripheral blood mononuclear cells (PBMCs) in MS was investigated. In addition, GM-CSF regulation was studied in the above-mentioned cells in MS. Finally, GM-CSF neutralization was performed in a phase Ib clinical trial, and some immune-related effects were investigated.